Analisys The Influence of Social Media on Product Purchasing Decisions - Dyah O Waluyani; Mei Sunday Simanjuntak; Veronica Lusianna Sitohang (Indonesian Development of Economics and Administration Journal, 2024)
This research is a literature study conducted through journal reviews and literature studies that are relevant to the research. The type of data used is secondary data, namely data obtained indirectly. Data collection techniques are carried out by reviewing and analyzing books and journals with rules related to the influence of social media, product purchasing decisions. From the research results, it is known that the use of social media is very important in influencing product purchasing decisions in the current industrial era. Human Resources of an organization, demanding the 5.0 era revolution and the current era of free competition, it is hoped that organizations must have quality, innovative and creative human resources. Because the organization is a network and decisions for succession policies and marketing decisions for quality products globally. Social media is used as a performance benchmark with the aim of getting loyal consumers and being able to promote the products they enjoy. The industrial revolution 5.0 has brought many changes, especially changes in very rapid technological developments which have greatly influenced the industrial world, namely that humans are required to master technology, especially for officials in companies who have direct contact with consumers throughout the world. And companies are also required to be able to follow technological developments and adapt them to global product marketing activities using social media. This speeds up the broader marketing process and improves employee performance